2018
DOI: 10.1088/1367-2630/aab32f
|View full text |Cite
|
Sign up to set email alerts
|

Quantum oscillations in the type-II Dirac semi-metal candidate PtSe2

Abstract: Three-dimensional topological semi-metals carry quasiparticle states that mimic massless relativistic Dirac fermions, elusive particles that have never been observed in nature. As they appear in the solid body, they are not bound to the usual symmetries of space-time and thus new types of fermionic excitations that explicitly violate Lorentz-invariance have been proposed, the so-called type-II Dirac fermions. We investigate the electronic spectrum of the transition-metal dichalcogenide PtSe 2 by means of quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The second term is the Drude term which refers to intraband transition of the free charge carriers while the third term is associated with the effect of interband transitions of the bound charge carriers. Previous studies have found that the concentration and the effective mass of the free charge carriers of bulk PtSe 2 are N = 1.7 × 10 20 cm -3 [22] and m * = 2.5m e , [23] respectively, where m e is the electron rest mass. Using these values, the plasma frequency ( p…”
Section: Far-field Ftir Spectroscopymentioning
confidence: 97%
“…The second term is the Drude term which refers to intraband transition of the free charge carriers while the third term is associated with the effect of interband transitions of the bound charge carriers. Previous studies have found that the concentration and the effective mass of the free charge carriers of bulk PtSe 2 are N = 1.7 × 10 20 cm -3 [22] and m * = 2.5m e , [23] respectively, where m e is the electron rest mass. Using these values, the plasma frequency ( p…”
Section: Far-field Ftir Spectroscopymentioning
confidence: 97%
“…Here, we investigate a TMD, 1T -PtSe 2 , whose ground state is not a semiconductor, but a semimetal. It has a metallic temperature-dependent resistivity [28], and as such would not typically be considered as a natural system for electrical gating. We nonetheless show that an electrostatic band bending potential can be created to screen a surface (or equivalently gate-induced) charge, which in turn confines a well-defined 2DEG.…”
Section: Introductionmentioning
confidence: 99%
“…The adjacent unoccupied Se layers are held together by weak van der Waals interactions. Theoretical calculations and ARPES show that the Fermi surface in PtSe 2 sits at >1 eV above the Dirac point 17,33 . The large ΔE hinders the detection of the chiral anomaly induced negative MR in the stoichiometric PtSe 2 .…”
Section: Resultsmentioning
confidence: 96%
“…As this material has been only recently explored, only a weak chiral negative MR of $À0:1% has been reported recently 32 . The in-depth transport measurements are still lacking 33 . As a transition metal dichalcogenide of 1T structural phase, PtSe 2 hosts a nonnegligible in-plane anisotropy, which may have an important role in its magnetotranport in addition to the chiral anomaly.…”
mentioning
confidence: 99%